The complete chloroplast genome sequence and phylogenetic analysis of Disporum viridescens (Liliaceae). Issue 6 (3rd June 2022) - Ye, Mingyan; Lang, Jiaqi; Yin, Fuqiang; Liu, Ming
Abstract: Disporum viridescens is a medicinal plant in three provinces of Northeast China. In this paper, we report the characteristics of the complete chloroplast genome (CP) of Disporum viridescens. We discuss mainly the phylogenetic relationship between this species and its relatives. The length of its sequence was 156, 645 bp, with a total GC content of 37.6% A large single-copy region (LSC) of 85, 103 bp, a small single-copy region (SSC) of 17, 964 bp, and a pair of inverted repeat (IR) regions of 26, 789 bp were detected in this study. The complete chloroplast genome sequence contained 127 genes, including 81 encoding, 38 transfer RNA (tRNA), and 8 ribosomal RNA (rRNA) genes. Our phylogenetic analysis results showed that Disporum viridescens is closely phylogenetically related to Disporum cantoniense of the family Colchicaceae.